Yield and Quality of Rice as Affected by Molybdenum Applied With Chemical Fertilizers and Organic Matter - Bala, P; Hossain, SMA (Journal of Agriculture & Rural Development, 2008)
A field experiment was conducted at the field laboratory of the Department of Agronomy, Bangladesh Agricultural University, Mymensingh to evaluate the effect of molybdenum (Mo) with recommenced chemical fertilizer and organic matter on yield and quality of rice cv. BRRI dhan 30. Three levels of Mo viz. 0, 100 and 200 ppm were applied with recommended dose of chemical fertilizers (80, 15, 40, 10, 1.5 kg ha-1NPKSZn) and organic matter as both cow dung and compost. Plant height, number of ear bearing tillers hill-1, straw yield and biological yield were maximum when 100 ppm Mo was applied with chemical fertilizer. Number of total spikelets panicle-1, grains panicle-1, nitrogen content, nitrogen uptake in grain and straw, and protein content in grain were recorded better when 100 ppm Mo was applied with cowdung. Those parameters were minimum when 0 ppm Mo was applied with either cowdung or compost or NPK. The best performance was obtained when 100 ppm Mo was applied either with recommended fertilizers or with cow dung/compost. The performance of rice with 200 ppm of Mo was better than no addition of Mo in respect of yield and yield contributing characters. Key words: Molybdenum, quality, rice, yield. doi:10.3329/jard.v6i1.1653 J Agric Rural Dev 6(1&2), 19-23, June 2008